2015
DOI: 10.1039/c5cc03322e
|View full text |Cite
|
Sign up to set email alerts
|

Organic alloys of room temperature liquids thiophenol and selenophenol

Abstract: The first examples of organic alloys of two room temperature liquids, obtained and characterized via in situ cryo-crystallography, are presented. Thiophenol and selenophenol, which exhibit isostructurality and similar modes of S⋯S and Se⋯Se homo-chalcogen interactions along with weak and rare S–H⋯S and Se–H⋯Se hydrogen bonds, are shown to form solid solutions exhibiting Veggard's law-like trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…magnitude smaller than the corresponding value in the BCP associated with the S•••S contact in the S--S_lat(HT) interaction. It is worth mentioning that the computed values of the electronic density in the BCPs associated with the S•••S contacts of HT and the shorter S•••S contacts of LT are very similar to the experimental value determined for the S•••S contacts in TiS2 77 and the computed values for other organic crystals featuring S•••S chalcogen interactions 78,79. …”
supporting
confidence: 80%
“…magnitude smaller than the corresponding value in the BCP associated with the S•••S contact in the S--S_lat(HT) interaction. It is worth mentioning that the computed values of the electronic density in the BCPs associated with the S•••S contacts of HT and the shorter S•••S contacts of LT are very similar to the experimental value determined for the S•••S contacts in TiS2 77 and the computed values for other organic crystals featuring S•••S chalcogen interactions 78,79. …”
supporting
confidence: 80%
“…The lattice parameters of C 6 H 6 Cl are very similar to (C 6 H 5 OH)Á0.5H 2 O and the principal difference on substitution of Br and I is an increase in the length of the a axis as the length of the carbon-halogen bond increases, these being roughly co-aligned with a in the same fashion as the C-O bond in phenol hemihydrate. Similarly, both thiophenol (JUJPEL; Thomas et al, 2015) and selenophenol (JUJPAH; Thomas et al, 2015) adopt the same packing as the phenol molecule in phenol hemihydrate. These are reported in space group Pnab rather than the conventional setting of Pbcn, otherwise the only meaningful difference is the presence of S-HÁ Á ÁS or Se-HÁ Á ÁSe chains long the crystal's a axis instead of rings of O-HÁ Á ÁO hydrogen bonds via H 2 O.…”
Section: Database Surveymentioning
confidence: 99%
“…Studies on H 2 S complexes in the gas phase suggest that the S-H donor behaves very similarly to O-H and N-H, irrespective of a large involvement of the dispersion interaction (Bhattacherjee et al, 2013;Bhattacharyya et al, 2013). Very few crystallographic studies have been reported in the literature (Steiner, 2000;Nangia & Desiraju, 1999;Thomas, Sathishkumar & Row, 2015) including a Cambridge Structural Database (CSD) analysis (Allen et al, 1997), which clearly establishes the significantly low number of examples for the occurrence of S-HÁ Á ÁS hydrogen bonds. Indeed, the current version of the CSD (Version 5.37, November 2015) has only 60 crystal structures which possess S-HÁ Á ÁS hydrogen bonds out of 160 organic molecules having S-H bonds.…”
Section: Introductionmentioning
confidence: 99%